Fat–water MRI separation using deep complex convolution network - Ganeshkumar, Moorthy; Kandasamy, Devasenathipathy; Sharma, Raju; Mehndiratta, Amit (Magma (New York, N.Y.), 2025)
Objective Deep complex convolutional networks (DCCNs) utilize complex-valued convolutions and can process complex-valued MRI signals directly without splitting them into two real-valued magnitude and phase components. The performance of DCCN and real-valued U-Net is thoroughly investigated in the physics-informed subject-specific ad-hoc reconstruction method for fat–water separation and is compared against a widely used reference approach. Materials and methods A comprehensive test dataset ( n = 33) was used for performance analysis. The 2012 ISMRM fat–water separation workshop dataset containing 28 batches of multi-echo MRIs with 3–15 echoes from the abdomen, thigh, knee, and phantoms, acquired with 1.5 T and 3 T scanners were used. Additionally, five MAFLD patients multi-echo MRIs acquired from our clinical radiology department were also used. Results The quantitative results demonstrated that DCCN produced fat–water maps with better normalized RMS error and structural similarity index with the reference approach, compared to real-valued U-Nets in the ad-hoc reconstruction method for fat–water separation. The DCCN achieved an overall average SSIM of 0.847 ± 0.069 and 0.861 ± 0.078 in generating fat and water maps, respectively, in contrast the U-Net achieved only 0.653 ± 0.166 and 0.729 ± 0.134. The average liver PDFF from DCCN achieved a correlation coefficient R of 0.847 with the reference approach.